Expandable polystyrene (EPS) foam filled epoxy composite / Rabiatul Manisah Mohamed - Mohamed, Rabiatul Manisah (2008)
In product packaging, the role of expanded polystyrene (EPS) is important for the protection of fragile goods, preventing them from shock and vibration. The EPS is also known as thermal insulator and lightweight but it is non-biodegradable. Increased demands in packaging lead to an increase in the volume and quantity of the waste in landfills. Some efforts have been made to recycle them to ease the problem. This study aims to recycle the EPS solid waste as fillers in epoxy matrix. Studies on the physical, mechanical and thermal conductivity of formed composites were conducted. The EPS waste was crushed and the EPS/Epoxy composite was prepared at ranges of composition from 20% to 80% (by Volume %) using compression moulding. It was found that the composite density decreased with an increase in filler loading from 1.136 to 0.468 g/cm3. The reduction was due to the lightweight of EPS since the combination of EPS and the Epoxy matrix resulted in air being incorporated in the composite. It also showed that the higher filler loading gave higher water absorption. More voids introduced in the composite with higher filler percentages encouraged the water absorption. For the mechanical properties, the tensile strength (15.52 to 1.30 MPa), strain (2.69 to 0.76 %) and Young’s modulus (1201.22 to 307.31 MPa) was found to decrease upon increase in filler content. Similar trend was also obtained for flexural strength (33.61 to 4.06 MPa) and flexural modulus (1074.20 to 466.14 MPa). These results were explained from the SEM micrographs which showed that the wall of EPS cellular structures did not collapse during fabrication. The gas phase which encapsulated throughout the composite acted as voids. The micrographs also revealed good adhesion between the EPS and Epoxy matrix. Despite the good adhesion, the EPS/Epoxy composite strength did not improve due to the effect of the air which filled the foam cellular structures. The thermal conductivity (0.1333 to 0.056 W/mK) was also found to be reduced for all filler content with increase in the heat supplied. However, the influence was small compared to the significant reduction in the thermal conductivity upon increase in the filler content. As the EPS content increased, the quantity of air trapped in the cellular structure also increased, making it more difficult to transfer heat, thus lowering the thermal conductivity. From the study, the EPS waste can be recycled through EPS/Epoxy composites and could be used as heat insulation material for dwelling.